(3oeYLe TjhN CHj GdaVd GdoHNGQjs - (3eQJVj GdRHjOj , eMeO Hf eMeO Hf eMeO Hf YHO GdQRGb GdMSjfj, CHh GdajV,J (B1205 (3g` s ((3GdeSLO GdCbUi s)
(3ChdgG (B:s
(3GdMeO ddg ceG jLH CaVGdg s
(3fSNI KGfjIs
(3hgh Rjf GdOjf CHhGdaVd eMeO Hf CMeO Hf eMeO GdMSjfj GdoHNGQjs
(3fbdkG Yf NW GdeDda hHBNQgG ELGRGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs